Modelo de decisão multicritério para auxiliar a priorização de vítimas no atendimento pré-hospitalar de emergência: o caso do SAMU/192 - Frazão, Talita Dias Chagas (2020)
Decisions about prioritizing victims in pre-hospital emergency care take place in a scenario of scarcity of resources, changes in patient demographics and professional development, making it difficult to make decisions in the Emergency Medical Services, SAMU/192. Making a decision without considering certain criteria can compromise the victim’s safety, access and quality of health. Therefore, it is necessary to find techniques and tools that include the criteria that guide and influence decisions, in order to reduce errors.In this environment, Multicriteria Decision Analysis is a tool to support decisions, and its use as a method to support the definition of priorities in health care has been growing in recent decades. Therefore, this research proposed and developed a multicriteria decision model to help prioritize victims, in the context of SAMU/192. For that, a systematic literature review was made, defining the limits of the problem, raising the evaluation criteria, and the FiTradeoff method was used to prioritize victims in SAMU/NatalRN. A survey of SAMU representatives from the Northeastern States revealed 25 criteria that guide the decision of the regulator, 10 were selected to choose a victim, among 4 calls at the SAMU/Natal-RN Regulation Center. This work contributed significantly to the rational, transparent and impartial practice of prioritizing victims of SAMU/192, using the multicriteria methodology to support the decision. Selecting and weighing the criteria in this study indicated that the protocols that guide regulatory physicians do not take into account all criteria for prioritizing victims in an environment of scarcity of resources. The model developed will support the SAMU/192’s regulator to direct resources to victims who most need support, and can be used in other pre-hospital emergency care units in other cities.